Prospects of Croatian initiative “The Baltic – Adriatic – Black Sea” - N. A. Samoylovskaya (Международная аналитика, 2017)
In January 2015 K. Grabar-Kitarovic was elected as President of Croatia. She identified the integration of Southeast Europe countries into European and Euro-Atlantic institutions and strengthening the cooperation between the countries of Central Europe as a national strategic interest. In her opinion the 12 European member countries of the EU located between the Adriatic, Black and Baltic seas have great potential for regional cooperation in the framework of the EU and the transatlantic community. This potential depends on the geographical position and features of common economic and cultural development. In the presented work is described the evolution of the concept of “the Baltic-Adriatic-Black Sea” and the prospects of its promotion in the countries of Eastern Europe. Special attention is paid to the impact of the initiative on the economic and strategic interests of Russia in Eastern Europe.